Hubungan Antara Status Gizi Dengan Menstruasi Dini Pada Siswi di SD Saraswati 3 Denpasar - I Gusti Ayu Istri Pradnya Dewi; Anak Agung Gede Budhitresna; Desak Putu Citra Udiyani (Aesculapius Medical Journal, 2024)
[Relationship Between Nutritional Status and Early Menstruation in Students at SD Saraswati 3 Denpasar] Early menstruation is increasingly showing an increase throughout the world, including in Indonesia. Bali Province ranks second after DKI Jakarta Province in cases of early menstruation, especially Denpasar City, which has a relatively high prevalence of early menstruation, reaching 26.7%. In the preliminary study that the researchers conducted at SD Saraswati 3 Denpasar, the majority of early menstruation was 40%. Excess nutritional status is often associated with earlier menstruation. This study aims to determine the relationship between nutritional status and early menstruation in female students at SD Saraswati 3 Denpasar. This research method is an observational analytic study with a cross-sectional design. The research subjects were SD Saraswati 3 Denpasar students who met the inclusion criteria with a total sample of 180 people using the total sampling method. The independent variable in this study was nutritional status, and the dependent variable was early menstruation. Research data were analyzed statistically in two stages: univariate and correlation tests with Spearmen-Rho. The P value is considered significant when P <0.05. This study found that age was obtained with an average of 9,56Â±1,13 years. The highest normal BMI was received by 80 female students (44,4%). Menstrual status was experienced by 77 female students (42,7%). The age of first menstruation was at the age of 11, with as many as 30 female students (16,7%). Based on the statistical test results, a moderate correlation was obtained with the results r = 0.462 and p = <0.001 (p < 0.05). This study's results indicate a significant relationship between nutritional status and early menstruation in female students at SD Saraswati 3 Denpasar.